Elements associated with moral deliberation in family health teams: in search of excellence in professional practice - Ferraz, Cecília Maria Lima Cardoso; Brito, Maria José Menezes (Saúde e Sociedade, 2022)
This single-case qualitative study aims to identify the elements associated with moral deliberation in the Family Health Strategy (ESF) by interviewing thirty-five professionals from family health teams. Data were collected via interviews guided by a semi-structured script and observation and analyzed using thematic content analysis. The results showed that moral deliberation in the concrete context of the practice of ESF professionals proved to be a subjective and incipient construction, influenced by factors internal and external to individuals. We concluded that identifying the elements that influence moral deliberation in the context of the ESF can favor the ethical improvement of health practices.